Factors Affecting Corporate Profitability - Fitriawati, Roza (Sean Institute, 2025)
This study aims to examine the influence of Capital Adequacy Ratio (CAR), Non-Performing Loans (NPL), Liquidity, and Leverage on Profitability. The research methodology used in this study is quantitative. The data utilized is secondary data obtained from www.idx.co.id. The population in this study consists of banking companies listed on the Indonesia Stock Exchange for the period 2018-2022, with a sample size of 23 companies. Data analysis for hypothesis testing is conducted using Multiple Linear Regression with the assistance of SPSS version 26 software. The results of the study indicate that Non-Performing Loans (NPL) and Leverage have a negative and significant effect on Profitability or Return on Assets (ROA), while Capital Adequacy Ratio (CAR) and Liquidity have no effect on Profitability or Return on Assets (ROA).